Mathematical models to estimate diet intake for Nile Tilapia (Oreochromis niloticus) and Tambaqui (Colossoma macropomum) (Research, Society and Development, 2021)
Precision technology is inserted into rural areas every day, and for that, research with mathematical models that can be adopted to improve management is necessary. This research aims to develop non-linear curves from equations consolidated in the scientific world for the consumption of diets for tambaqui and Nile tilapia. By obtaining information on growth over time and food supply tables for each growth phase for the studied fish species, we proceeded to draw up growth curves over time and their food consumption. Based on the data collected, the parameters of the equations of four nonlinear models (Gompertz and Logistic) were estimated for the two studied variables (Growth in weight (g) over time and Food consumption (g) over time. over time). Adjustment evaluators (biological interpretation and analysis of studentized residues) were adopted to select and verify the quality of the models. The data generated on the supply or consumption of feed for Nile tilapia and tambaqui fit the Gompertz and Logistic models, respectively. These models can be used to estimate feed consumption or supply for Nile tilapia and tambaqui, but strict evaluation and adjustment criteria are required.